Using Machine Learning to Predict Primary Care and Advance Workforce Research during the Early Stages of the Covid-19 Pandemic: A Review - Khalida Gulfam, Kashif Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Primary care is the first line of defense during a pandemic. It can assist patients manage at home, reinforce public health messaging, and pinpoint individuals who require hospital treatment. Primary care struggled to quickly adapt in order to safeguard doctors, staff, and patients during the COVID-19 outbreak and maintain patient relationships. We outline the steps primary care has to follow in a pandemic using the existing public health framework for doing so. Study Design: It was a review. The authors' primary care practices and networks' observed experiences are used to guide the recommended activities. During the early stages of the COVID-19 pandemic, efforts were concentrated on encouraging physical separation and urging patients who had a suspected sickness or exposure to self-quarantine. Both testing and contract tracing were not accessible. Place and Duration: It was conducted at services hospital Lahore and duration was 07 months. Telehealth was used to transform in-person treatment into virtual care as the epidemic progressed. By utilizing registries to connect with people who were socially vulnerable, at risk for infection, or had chronic diseases that were not under control, practices maintained contact with their patients. Most individuals with probable COVID-19 were treated by practices at home. Results: Practices are currently getting ready to deal with the direct and indirect effects of the pandemic, including complications from COVID-19 infections, missed treatment for acute issues, insufficient prevention, uncontrolled chronic disease, mental illness, and increased social requirements. Conclusion: Throughout, practices suffered from severe financial strain, firing employees or sometimes shutting down when it was most required. In order to prepare for the upcoming pandemic, primary care must draw lessons from this experience. Primary care cannot be neglected by payers or policymakers in their time of need. Keywords: covid-19, pandemic, primary care, Machine Learning and advance workforce research